2020
DOI: 10.1596/34802
|View full text |Cite
|
Sign up to set email alerts
|

Where is the Money Coming From? Ten Stylized Facts on Financing Social Protection Responses to COVID-19

Abstract: Since the onset of the COVID-19 health crisis, and associated stringency measures, governments have acted in support of businesses and individuals by activating fiscal stimulus measures and introducing or expanding social protection programs. Initiatives to collect, analyze and monitor social protection responses have generated a wealth of evidence on the most aspects 1 The note presents preliminary findings for discussion and only reflects the personal views of the authors. We are grateful to Penny Williams, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Many wealthier states put themselves on a quasi‐war footing, adopting a “whatever it takes” mentality to prevent poverty, deprivation and to guarantee survival, although only over the short term. States deployed massive amounts of resources to the emergency response – Japan, for example, committed an unprecedented 42 per cent of its GDP to fiscal stimuli in 2020 (Almenfi et al, 2020).…”
Section: A New Precedent For State Intervention As the Guarantor Of L...mentioning
confidence: 99%
“…Many wealthier states put themselves on a quasi‐war footing, adopting a “whatever it takes” mentality to prevent poverty, deprivation and to guarantee survival, although only over the short term. States deployed massive amounts of resources to the emergency response – Japan, for example, committed an unprecedented 42 per cent of its GDP to fiscal stimuli in 2020 (Almenfi et al, 2020).…”
Section: A New Precedent For State Intervention As the Guarantor Of L...mentioning
confidence: 99%
“…By February 2022, the six largest countries in South Asia had implemented 159 Social Protection and Labor measures. An estimated 79% of aid disbursed was in the form of social assistance and 11% each was directed to social insurance and to labor market assistance (Almenfi & Iyengar, 2022). These countries had ramped up expenditure on assistance to 1.8% of Gross Domestic Product in 2021-22, compared to 1.13% of F I G U R E 1 COVID-19 stringency index in South Asian countries.…”
Section: Bangladeshmentioning
confidence: 99%
“…Despite the rapid and significant expansion, in general, these measures were inadequate (see Drèze and Somanchi (2021a) for a discussion of India). Overall, the South Asia region spent US $46 per capita (unadjusted for Purchasing Power Parity) relative to the US$314 per capita in the 194 countries for which these data were compiled (Almenfi & Iyengar, 2022).…”
Section: Bangladeshmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Recent review of how governments in East Asia and the Pacific have financed their social protection responses to COVID-19 found that most countries have funded expanded programs through internal budget reallocations or by increasing deficit spending-although at least a couple of countries (Fiji, Indonesia) have taken on multilateral debt to finance their social protection responses (Almenfi et al 2020; World Bank forthcoming).…”
Section: Box Iib2 Eap Countries' Social Protection Responses To Covid-19mentioning
confidence: 99%